Frações: Uma proposta de ensino-aprendizagem com o uso de rotação por estações - Adriana Matsuura de Oliveira (2024)
In this work, we present a teaching proposal for the basic concepts of Fractions using Active Methodologies for 6th-grade elementary school students. This study was designed based on the Station Rotation Model, and the use of digital technologies was incorporated in two out of four learning stations. The Wordwall platform was used as a technological resource for the development of these two virtual learning environments, which enabled the implementation of our teaching proposal in the classroom. We highlight that the application of our teaching proposal in the classroom resulted in favorable student outcomes, as the station rotation model significantly contributed to the learning of Fractions and promoted a more dynamic, interactive, and engaging lesson. Furthermore, it was observed that students demonstrated considerable improvement in cooperation, autonomy, proactivity, and group collaboration. The challenges encountered included the need for detailed planning and efficient management of technological resources, as well as the continuous training of teachers for the effective use of these methodologies. Nonetheless, in light of the positive results presented, future prospects have emerged for the continuation of this work in the context of using digital technologies and the station rotation model for new teaching-learning proposals in mathematics. Keywords: Fraction; active methodologies; teaching-learning; station rotation; digital technologies.